Sex Hormone Profiles And Anthropometric Parameters Of Post Menopausal Breast Cancer Patients - Akalanka, H.M.K.; Ekanayake, S.; Samarasinghe, K. (Proceedings of the Young Scientist Forum Symposium, 2015)
Attached